Synthesis and characterization of novel value added biodegradable poly(aleuritic acid) from renewable resources(shellac) and invertible amphiphilic behaviors in various solvents - Pandey, Asutosh K.; Nande, Smita S.; Selukar, Balaji S.; Garnaik, Baijayantimala (E-Polymer, 2010)
A novel biodegradable polymer poly(aleuritic acid) (PAA) ( M̄w 120,000) was prepared from aleuritic acid, which was obtained from renewable resources (Lac) by using tin catalyst. Aleuritic acid (AL) was protected at 9, 10 position by dimethoxy propane. The protected AL (Pro.AL) was further polymerized to obtain linear protected polyaleuritic acid (PAL) by dehydropolycondensation. Effects of various kinetic and thermodynamic parameters were studied. After polymerization, the deprotection of PAL was carried out. The synthesized PAL and PAA were characterized by using various techniques such as FT-IR, LC-MS, SEC, NMR (1H and 13C), 13C CP/MAS (Cross Polarization / Magic Angle Spinning) of solid PAA, DSC, SEM and TEM etc. The micelle and inverted micelle -structure in polar and nonpolar solvents are highlighted

Synthesis of ciprofloxacin-conjugated poly(L-lactic acid) polymer for nanofiber fabrication and antibacterial evaluation - Parwe, Sharad P.; Chaudhari, Priti N.; Mohite, Kavita K.; Selukar, Balaji S.; Nande, Smita S.; Garnaik, Baijayantimala (International Journal of Nanomedicine, 2014)
Ciprofloxacin was conjugated with polylactide (PLA) via the secondary amine group of the piperazine ring using PLA and 7-(4-(2-Chloroacetyl) piperazin-1-yl)-1-cyclopropyl-6-fluoro-1, 4-dihydro-4-oxoquinoline-3-carboxylic acid. Zinc prolinate, a biocompatible catalyst was synthesized, characterized, and used in ring opening polymerization of L-lactide. Five different kinds of OH-terminated poly(L-lactide) (two-, three-, four-, six-arm, star-shaped) homopolymers were synthesized by ring opening polymerization of L-lactide in the presence of dodecanol, glycerol, pentaerythritol, dipentaerythritol as initiator and zinc prolinate as a catalyst. The structures of the polymers and conjugates were thoroughly characterized by means of gel permeation chromatography, matrix-assisted laser desorption/ionization-time of flight mass spectrometry, and nuclear magnetic resonance spectroscopy. PLA (molecular weight = 100,000) and ciprofloxacin conjugated PLA were used for fabrication of nonwoven nanofiber mat (diameter ranges; 150-400 nm) having pore size (62-102 nm) using electrospinning. The microbiological assessment shows that the release of ciprofloxacin possesses antimicrobial activity. The drug-release behavior of the mat was studied to reveal potential application as a drug delivery system. The result shows that the ciprofloxacin release rates of the PLA conjugate nonwoven nanofiber mat could be controlled by the drug loading content and the release medium. The development of a biodegradable ciprofloxacin system, based on nonwoven nanofiber mat, should be of great interest in drug delivery systems.
Keywords: antibacterial activity; ciprofloxacin conjugated polylactides; CP-PLA; drug release; electrospinning; MDR; nonwoven nanofibers; zinc prolinate

Synthesis of amine-loaded styrene–divinylbenzene copolymers for carbon dioxide capture - Nande, Smita S.; Garnaik, Baijayantimala (ACS Engineering Au, 2025)
Carbon dioxide capture by various tertiary amines and quaternary bulky ammonium salts loaded in cross-link hybrid polymer (styrene–divinylbenzene copolymer) was explored. These polymeric materials were prepared by suspension polymerization in one pot using monomers like styrene and divinylbenzene in the presence of various amines to obtain uniform spherical beads. The homopolymer was separated from the cross-link hybrid product by Soxhlet extraction. The synthetic strategy is cost-effective and user-friendly, can be easily scaled up for production, and confirms better mechanical strength. The amine-loaded microporous polymeric spheres displayed a microsphere size of 5.2 nm with a high surface area of ∼25–310 m2 g–1. These hydrophobic polymeric spherical beads were thermally stable up to 200 °C. The quaternary ammonium group salt (bulky)-loaded beads presented high carbon dioxide uptake (up to ∼16.4 wt % at 273 K /1.0 bar) due to the presence of lone pair electrons of the heteroatom, which might improve the interaction between the polymeric matrices and CO2 molecules through local-dipole/quadruple interactions. In the case of tertiary amines, a high uptake of carbon dioxide (up to ∼15.2 wt % at 273 K /1.0 bar) was achieved, which is attributed to the formation of bicarbonate, as there may be the possibility of the presence of little moisture in the system, which facilitates the interaction. These hybrid polymeric materials exhibited a better storage capacity of CO2.